1971
DOI: 10.2466/pr0.1971.28.2.483
|View full text |Cite
|
Sign up to set email alerts
|

Factors of Interpersonal Behavior and Judgment in Social Groups

Abstract: This study explored dimensions which are used to describe persons within closely-knit social groups. Ss in the group were similar in socio-economic starus and used w o independent dimensions in describing one another: another's positive and ncgative reinforcing quality. The sociometric questionnaire which yielded these two factors is a potentially useful device for characterizing an individual within any social organization according to a four-fold classification: positively and negatively reinforcing to other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1975
1975
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…These and other variables loaded on a factor labeled affiliative behavior. A second study by Mehrabian and Ksionzky (1971) found much the same pattern of factor loadings for the same variables as those used in the Mehrabian study. It is interesting to note that in both of these factor analyses, distance between the interactants was not associated with the affiliative behavior factor.…”
Section: Nonverbal a Ffiliative Expressiveness And Uncertaintysupporting
confidence: 56%
See 1 more Smart Citation
“…These and other variables loaded on a factor labeled affiliative behavior. A second study by Mehrabian and Ksionzky (1971) found much the same pattern of factor loadings for the same variables as those used in the Mehrabian study. It is interesting to note that in both of these factor analyses, distance between the interactants was not associated with the affiliative behavior factor.…”
Section: Nonverbal a Ffiliative Expressiveness And Uncertaintysupporting
confidence: 56%
“…Existing evidence relevant to the relationship posited by the theorem will be cited. The relationship suggested by Theorem 1 has been verified in at least two factor analytic studies (Mehrabian, 1971a;Mehrabian & Ksionzky, 1971).…”
Section: Theoremsmentioning
confidence: 71%
“…Aside from Mehrabian's (1971) and Mehrabian and Ksionzky's (1971) findings, there are grounds for expecting a positive association between nonverbal affiliative expressiveness and amount of verbal communication. Speakers regularly employ nonverbal affiliative cues, such as head nods and arm gestures, to compliment and emphasize verbal messages.…”
Section: Nonverbal Aff Iliative Expressivenessmentioning
confidence: 77%
“…If nonverbal affiliative expressiveness and amount of verbal communication are positively related, the earlier proposed alteration of the verbal communication-uncertainty relationship suggests changes in Axiom 2. Aside from Mehrabian's (1971) and Mehrabian and Ksionzky's (1971) findings, there are grounds for expecting a positive association between nonverbal affiliative expressiveness and amount of verbal communication. Speakers regularly employ nonverbal affiliative cues, such as head nods and arm gestures, to compliment and emphasize verbal messages.…”
Section: Nonverbal Aff Iliative Expressivenessmentioning
confidence: 92%
See 1 more Smart Citation